Razumevanje i produkcija imenica i glagola kod dece govornika srpskog jezika - Milošević, Neda; Arsenijević, Bojan (Specijalna edukacija i rehabilitacija, 2025)
Introduction. Comprehension and production of nouns and verbs play a key role in children’s further language acquisition, as they are among the first words in their vocabulary and serve as indicators of their development. Although they are among the frequently examined categories in languages around the world, they continue to attract attention today due to their importance in identifying phenomena and shapes in a child’s experience and development. Aim. The paper presents the results of a study on the comprehension and production of nouns and verbs in Serbian-speaking preschool children. Method. The effects of word class, gender, socioeconomic factors, and lexical category on the understanding and production of one word were tested in 523 preschool-age participants using toys and picture books. Results. The results are consistent with previously established patterns and tendencies: girls had better results than boys; higher education of parents, a greater economic development of the region, and smaller differences between the local dialect and the standard language all had a positive influence on language acquisition; and competence was better for nouns than for verbs. Conclusion. Further research should focus on analyzing less frequent nouns and verbs in order to avoid the ceiling effect, as well as on a more consistent balancing of stimulus features, particularly concreteness and abstractness (by choosing abstract nouns).